The Development of Oil-Fueled Gas Steam Stove as a Learning Media to Enhance Students' Curiosity - Ketut Alit Adi Untara; Gustina Gustina; Ielda Paramita (Universitas Lambung Mangkurat, 2021)
This study aims to develop learning media in the form of gas steam stoves fueled by oil and describe the validity and effectiveness of the products being developed. This development and research are summarized in a study entitled the development of learning media in a gas-fired gas stove to increase students' curiosity in applied physics subjects. This study uses a media development research method known as Research and Development (R&D). From the research carried out, the following data were obtained: the results of media validation obtained very good categories, and validation test by media experts found very good category. In the curiosity test, which was initially limited to active students, the scores were very good. The results of the initial average curiosity test for the field test were obtained in the low category, and after the use of the media was tested again, and the average score was obtained in the very good category. It can be concluded that the use of an oil-fired gas steam stove in the form of a Pertamax stove as a learning medium can increase students' curiosity about learning applied physics material.